SUPERVISION OF HOTEL APPLICATIONS IN BANDA ACEH CITY : Study Of Sharia Labeled And Non Labeled Hotels - Nufus, Zakiatun; Yahya, Faisal; Mustaqilla, Safira (Al-Iqtishadiah: Jurnal Hukum Ekonomi Syariah, 2024)
This study aims to determine the use of labeling for sharia hotels in Banda Aceh City, todetermine the halal guarantee for hotels that are not labeled as sharia in Banda Aceh City,and to comply with supervision of sharia regulations in hotels in Banda Aceh City. In thisstudy the author uses a qualitative research method with a descriptive pattern. Data werecollected through interviews, documentation, and literature studies. Data analysis focuseson the labeling of sharia hotels in Banda Aceh City ( study of Sharia Labeled And NonLabeled Hotels). The results of the study indicate that to obtain labeling the hotel must obtaina permit and maintain order, although not all hotels in Banda Aceh City have sharialabeling, but they also comply with sharia rules and they also prohibit guests who are notnon-muhrim couples. The halal guarantee system for sharia hotels that refers to a series ofhotel rules or policies and procedures applied to hotel operations must be in accordancewith sharia principles. Supervision of hotels in the Banda Aceh city o focuses on shariaregulations, namely to ensure comfort for visitors. and see the halalness of products andprovide services that support business actors in obtaining halal certification.